Does schistosome infection affect behavior through the gut-brain axis? - Leigh Combrink; Johannie M Spaan; Alexis Perret; Thomas Maehara; Britney Hyun; Dana Parker; Jennifer L Johns; Michael S Blouin; Kathy Magnusson; Michelle L Steinauer (PLoS Neglected Tropical Diseases)
Parasitic helminths infect over 2 billion people, primarily those living in poverty. Helminth infections typically establish in early childhood and persist through critical periods of growth and development, leading to cognitive deficits and/or behavioral changes. These deficits could result from the helminths themselves or due to dysbiosis of the gut microbiota and its influence on the gut-brain axis. Using two cohorts of 3-week-old female mice, we measured levels of anxiety, fear, compulsion, spatial learning, and spatial memory, between schistosome-infected and sham-exposed mice. Additionally, we compared their fecal microbiomes using 16S rRNA gene sequencing at two time points during the chronic stage of infection. Schistosome-infected mice showed higher levels of anxiety in the open field test, reduced spatial learning in the Morris water maze task, and enhanced memory retention in the novel object task. All mice performed equally on the marble bury task. Each cohort started with unique microbiota which showed marked changes in the beta diversity of their microbiota after exposure. In both cohorts, at 7- weeks post exposure, infected mice had more Alistipes sp. and Bacteroides thetaiotaomicron and less Turicibacter sp. and Ligilactobacillus sp. than uninfected mice. At 10 weeks, infected mice had more Alistipes sp. and fewer Muribaculaceae sp. Interestingly, taxon shifts in infected mice were those typically associated with protective effects on liver disease and IL-10 gut conditions, suggesting a possible protective role of the shifted microbiome. Our analyses did not indicate associations between behavioral measures and microbiome composition; however, this could be due to the strong impact of infection on the microbiome composition. Findings here uncover behavioral and cognitive impacts of schistosome infection and shed light on the complex interplay between schistosome infection, behavioral changes, and host microbiome composition, which could ultimately support future global health efforts.